The influence of high-intensity run duration on tibial acceleration and shock attenution - Clansey, A.; Hanlon, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to investigate the effects of high-intensity fatiguing running on tibial acceleration and shock attenuation. Fourteen highly-trained male runners volunteered and completed an incremental treadmill-based lactate threshold test. On a subsequent test day, tibial acceleration and head acceleration values were recorded in all runners during two 20-minute treadmill running bouts at each subject's lactate threshold (3.5mM) speed. Results indicated no significant change in tibial acceleration during the running bouts, however head acceleration did significantly increase (38%) over time. This resulted in an overall decrease in shock attenuation due to the fatiguing running. The results indicate that these highly-trained runners may show improved movement strategies that allow them to maintain tibial acceleration rates even in a fatigued state.